How Long-Married Couples Stabilize Relationship Crises: A Phenomenological Study of Self-Managed Relational Processes - Nadia Ismoyorini; Pradipta Christy Pratiwi (Universitas Ahmad Dahlan, 2026)
This study examines how long-married couples sustain relational stability amid severe crises through self-managed processes of stabilization. Using a qualitative phenomenological approach, data were collected through sequential dyadic and individual interviews with three couples married for 25–28 years who perceived themselves as having successfully navigated past conflicts. Thematic analysis was employed to capture recurring patterns while preserving the relational and contextual nature of participants’ experiences. Findings indicate that marital resilience operates through a dynamic stabilization process involving (1) cognitive reframing, (2) emotional first aid through strategic silence, (3) dyadic repair to restore relational warmth, (4) intrapersonal ego-adjustment, and (5) structural role flexibility. Notably, silence is reinterpreted as an active regulatory practice embedded in relational contexts. The study also highlights asymmetrical emotional labor within couples, suggesting that stability is often maintained through unequal adaptive efforts. These findings extend conventional coping frameworks by conceptualizing resilience as an ongoing process of relational stabilization rather than discrete conflict resolution.